Hubungan Antara Kecerdasan Emosional dengan Motivasi Belajar Siswa pada Mata Pelajaran PAI: Survei di SMAN 1 Cikarang Barat - Anita Listiana; Yayat Suharyat (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2016)
This study aims to investigate the relationship between emotional intelligence and students' motivation on the subjects of PAI in SMAN 1 Cikarang Barat. The method used is quantitative survey method with the correlational approach. The population in this study were students of class X SMAN 1 Cikarang Barat numbered 400 students. While the sample in this study were 80 students by random sampling technique. The results showed that there is a positive relationship between emotional intelligence and motivation to learn by regresi Ŷ = α + bx, then Y = -30.09 + 1.15x and test correlation coefficient of 0.977. This suggests that emotional intelligence contributed 95.45%. The test results significant to the r value obtained for 0977 was significant at the level α = 0:05 to table the results count r r = 0.977 and r table = 0212, then significant. Thus, it can be concluded that the hypothesis that there is a relationship between emotional intelligence and motivation to learn in SMAN 1 Cikarang Barat